EFFECT OF A MIXTURE OF PORTLAND CEMENT 1 AND VOLCANIC ASH AS A STABILIZING MATERIAL ON SOIL CLAY WITH UCT TEST: PENGARUH CAMPURAN SEMEN PORTLAND 1 DAN ABU VULKANIK SEBAGAI BAHAN STABILISASI PADA TANAH LEMPUNG DENGAN UJI UCT - Daniel (UPMI Proceeding Series, 2023)
This research aims to determine the effect of a mixture of Portland cement 1 and volcanic ash as a stabilization material on clay soil using the Uct test. This research was carried out on soil samples that were not given stabilization materials (original soil) and on soil that was given chemical stabilization materials in the form of the addition of Portland Cement (PC) and Volcanic Mountain Ash (AGV) in various mixtures. The preparation of test objects is divided into several types according to each test with a fixed cement and ash content for all tests. The soil used is soil that has been filtered with sieve No. 40. Then the soil is weighed at 500 grams for one test object and put in plastic. After all the data is obtained from both physical and mechanical properties testing, data collection is then carried out. After the data is collected, data analysis is carried out. All results obtained from conducting research will be displayed in the form of tables, relationship graphs and explanations. From the experimental results, the soil compressive strength value for the original soil was 1.34 kg/cm2, while for the remoulded soil it was 0.51 kg/cm2. Figure 4.12 shows a comparison of the compressive strength values ​​of soil (qu) with the addition of 2% PC with varying levels of AGV addition. From the experimental results at levels of 2% - 24% AGV experienced an increase in the compressive strength value of the soil. This increase in soil compressive strength is due to the absorption of water by cement and ion exchange reactions which form calcium silicate and calcium aluminate which results in increased soil strength.